Self‐Assembly of Oriented Antibody‐Decorated Metal–Organic Framework Nanocrystals for Active‐Targeting Applications. Issue 21 (2nd January 2022) - Alt, Karen; Carraro, Francesco; Jap, Edwina; Linares‐Moreau, Mercedes; Riccò, Raffaele; Righetto, Marcello; Bogar, Marco; Amenitsch, Heinz; Hashad, Rania A.; Doonan, Christian; Hagemeyer, Christoph E.; Falcaro, Paolo
Abstract: Antibody (Ab)‐targeted nanoparticles are becoming increasingly important for precision medicine. By controlling the Ab orientation, targeting properties can be enhanced; however, to afford such an ordered configuration, cumbersome chemical functionalization protocols are usually required. This aspect limits the progress of Abs‐nanoparticles toward nanomedicine translation. Herein, a novel one‐step synthesis of oriented monoclonal Ab‐decorated metal–organic framework (MOF) nanocrystals is presented. The crystallization of a zinc‐based MOF, Zn2 (mIM)2 (CO3 ), from a solution of Zn 2+ and 2‐methylimidazole (mIM), is triggered by the fragment crystallizable (Fc) region of the Ab. This selective growth yields biocomposites with oriented Abs on the MOF nanocrystals (MOF*Ab): the Fc regions are partially inserted within the MOF surface and the antibody‐binding regions protrude from the MOF surface toward the target. This ordered configuration imparts antibody–antigen recognition properties to the biocomposite and shows preserved target binding when compared to the parental antibodies. Next, the biosensing performance of the system is tested by loading MOF*Ab with luminescent quantum dots (QD). The targeting efficiency of the QD‐containing MOF*Ab is again, fully preserved. The present work represents a simple self‐assembly approach for the fabrication of antibody‐decorated MOF nanocrystals with broad potential for sensing, diagnostic imaging, and targeted drug delivery. Abstract : A method for the integration of oriented antibodies in MOFs is proposed. A synchrotron small angle X‐ray scattering investigation demonstrates that the formation of the MOF (ZIF‐C) is induced by the crystallizable fragment region (Fc) of antibodies, leaving the fragment antigen‐binding (Fab) regions free to target antigens. ZIF‐C*antibody particles are functionalized with fluorescent markers for active targeting and cancer cell imaging.